(untitled) (Journal of Computational Mathematics, 2018)
The main aim of this paper is to show that the quadrilateral mesh condition RDP(N,ψ) is only sufficient but not necessary for the optimal order error estimate of the Q_1 isoparametric element in the H^1 norm.